Pendampimgan Pembiasaan Sholat Dhuhur Berjamaah sebagai Strategi Penanaman Nilai Kedisiplinan Siswa (Studi Kasus di SDN Sahang, Kecamatan Ngebel, Kabupaten Ponorogo) - Yuli Pernawati; Syamsul Wathoni (Social Science Academic, 2025)
Developing disciplined character from an early age through structured religious activities is a crucial aspect of character education. The Participatory Action Research (PAR) method directly involves teachers, researchers, and students in mentoring activities. The purpose of this community service is to foster consistent worship habits in students, instill discipline through regularity in the timing and procedures for congregational prayer, and strengthen synergy between teachers, students, and the community in developing religious character. Congregational prayer is not only understood as an obligatory act of worship but also as a means of character education that fosters discipline, responsibility, and togetherness. The research results indicate that the habit of congregational Dhuhr prayer has a positive effect on developing student discipline, as evidenced by regular attendance on time, adherence to the rules of worship, and consistency in carrying out obligations together. Furthermore, this activity also strengthens religious culture within the school environment. Thus, congregational prayer can be an effective strategy for instilling discipline and fostering students' religious character.